Effects of forming temperature and sintering rate to the final properties of FeCuAl powder compacts formed through uniaxial die compaction process - Rahman M.M.; Ismail M.A.; Sopyan I.; Rahman H.Y. (Institute of Physics Publishing, 2023)
Aluminum alloys; Argon; Compaction; Copper alloys; Iron alloys; Manufacture; Powders; Ternary alloys; Elemental powders; Elevated temperature; Experimental investigations; Forming temperature; Heating/cooling rate; Powder compacts; Sintered samples; Uniaxial die compaction; Sintering